2003
DOI: 10.1136/ijgc-00009577-200301000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with stereotactic radiosurgery for brain metastases of endometrial carcinoma: A case report and review of the literature

Abstract: Brain metastases from endometrial carcinomas are rare and the treatment is usually difficult. Here, we report a patient with stage IV endometrial carcinoma whose brain metastases showed complete remission after stereotactic radiosurgery using a gamma-knife. A 48-year-old woman underwent removal of a single brain metastatic lesion, and one month later underwent hysterectomy for endometrioid-type G3, endometrial adenocarcinoma. After hysterectomy, a cranial magnetic resonance imaging (MRI) demonstrated multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 28 publications
2
17
0
1
Order By: Relevance
“…In agreement with the reports of other authors, in the treatment of our group of patients with HM to the brain, surgery, stereotactic radiotherapy, WBPR, and WBRT were used [14,15,18,22,26,32,33,36,38,43,46,49,50]. The median survival of 10 patients was 4 months (range, 1-68 months); 2 patients treated with surgical resection and WBRT survived 60 months.…”
Section: Hm To the Brainsupporting
confidence: 74%
See 1 more Smart Citation
“…In agreement with the reports of other authors, in the treatment of our group of patients with HM to the brain, surgery, stereotactic radiotherapy, WBPR, and WBRT were used [14,15,18,22,26,32,33,36,38,43,46,49,50]. The median survival of 10 patients was 4 months (range, 1-68 months); 2 patients treated with surgical resection and WBRT survived 60 months.…”
Section: Hm To the Brainsupporting
confidence: 74%
“…Long-term survival is rare but has been documented in some patients with solitary brain lesions who underwent surgical resection and WBRT [15,32,43,45,50]. Prognosis is generally poor due to the widespread disease that usually accompanies the appearance of brain metastases [15,18,36,46]. Data from the literature and our own observations indicate that conventional surgery or stereotactic radiotherapy followed by WBRT is a cornerstone treatment for patients with HM to the brain from EC, especially in patients with solitary lesions, wellcontrolled extracranial disease, and good performance status [14,50].…”
Section: Hm To the Brainmentioning
confidence: 99%
“…However, it has been suggested that when all lesions are resectable, survival rates are equal for patients harboring solitary versus those with multiple brain metastases. SRS was used by Shiohara et al in their report of the successful treatment of 1 patient with multiple brain metastases from endometrial carcinoma 25. This limited experience is supported by multiple lines of evidence suggesting that SRS is beneficial for the treatment of multiple or unresectable brain metastases, regardless of the tumor histology.…”
Section: Discussionmentioning
confidence: 99%
“…This review revealed 16 patients from nine published studies who underwent surgery for brain metastases from endometrial cancer (107)(108)(109)(110)(112)(113)(114)(115)(116) (Table 7). Six of seven patients with stage IV disease had brain metastasis at diagnosis, and the seventh developed brain metastasis 3 months after bone metastasis at primary diagnosis.…”
Section: Cns Metastasesmentioning
confidence: 99%
“…Median overall survival for all 16 patients was 15.0 months (range 0.7-171 months) and that for patients with stage I-III disease was 8.0 months (range 0.7-84 months). The seemingly better survival among the seven patients with stage IV disease undoubtedly Alive with disease Shiohara (110) Alive, no evidence of disease Mahmoud (114) Alive, no evidence of disease Petru (107) Surgery in metastatic gynecological cancer 417 reflected the inclusion of two unusual cases. In one of these cases, the patient had three rounds of surgery or stereotactic radiosurgery plus chemotherapy for recurrent brain lesions and survived for more than 3 years (110) ; in the other case, a patient survived for 171 months despite having had an incomplete resection and brain lesions that persisted radiologically after chemotherapy and hormonal treatment (107) .…”
Section: Cns Metastasesmentioning
confidence: 99%